The Mediating Role of Academic Self-Efficacy Perception in the Relationship Between Family Emotional Atmosphere and Family Flexibility With Academic Achievement and Academic Procrastination in Students With Learning Disabilities - Jaber, Ali Mohsin; Mahdad, Ali; Salman Gatfan, Muntadher; Golparvar, Mohsen (KMAN Counseling & Psychology Nexus, 2024)
Parental involvement at home is essential for adapting to the learning process in children with learning disabilities. Unfavorable attitudes and responses of parents toward learning disabilities can lead to adjustment problems, low self-efficacy, and poor academic performance in children. This study aimed to examine the effect of family emotional atmosphere and family flexibility on academic achievement and procrastination, considering the mediating role of academic self-efficacy perception in students with learning disabilities. The statistical population included third- and fourth-grade students in Dhi Qar Province during the 2024 academic year. Among them, 125 students were selected using a multi-stage cluster random sampling method. Data were collected using the Family Emotional Atmosphere Questionnaire (Hillburn, 1964), Family Flexibility Scale (Shakery, 2003), Academic Achievement Scale (Wells, 2010), Academic Procrastination Scale (Solomon & Rothblum, 1984), and Academic Self-Efficacy Scale (Jinks & Morgan, 1999). Data were analyzed through Pearson correlation and structural equation modeling using SPSS-21 and AMOS-23 software. Results indicated that the variables of family emotional atmosphere and family flexibility indirectly affect academic achievement and procrastination through the perception of academic self-efficacy (p < .01). Based on the findings, it can be concluded that families and caregivers of children with learning disabilities should participate in advanced educational programs to gain a comprehensive understanding of these disabilities. This approach can help them foster their children's academic skills, perception of academic self-efficacy, and emotional support.